Efficacy of a combined live attenuated canine distemper and inactivated rabies vaccine in dogs - REDDY, G S; KALANIDHI, A P; SRINIVASAN, V A (The Indian Journal of Animal Sciences, 2013)
Combined live attenuated canine distemper (CD) and inactivated rabies vaccines were tested for their efficacy by assessing serum neutralizing antibodies against CD and rabies virus, and by challenge with virulent CD virus. Serological response induced by rabies vaccine alone and CD vaccine alone were comparable with that induced by combined rabies and CD vaccine. Dogs vaccinated with CD vaccine alone and combined CD and rabies vaccine resisted challenge with virulent CD virus. These results indicated that combined vaccine is effective in protecting dogs agamst CD infection and induces satisfactory serological response to both CD and rabies virus.